O desafio da moradia: a reprodução da habitação popular no espaço urbano de Mossoró (RN) na vigência do Estatuto da Cidade (2001-2011) e suas questões socioespaciais - Oliveira, Jionaldo Pereira de (2013)
This research defined as an object of study in this popular residential urban area of Mossoró-RN as representative of the social processes in term of the Law 10.257/2001, known as the City Statute. This assumption, we analyzed the spatial fundamentals that affect social housing in Mossoró between 2001 and 2011. The approach of housing in the geographic space does not dispense with the assumption that its expression is also a reflection of the dynamic social, economic and political, and even cultural, inherent spatial reproduction of society. The hegemony of the market economy has as part of its context the complexity imposed by its contingencies. In situations in which social inequalities are significant, such as Brazil, the intricate balance of forces that characterizes the spatial planning has a reference in housing consistent with their reasons. Alluding to this point the Brazilian context, it was found in many expressions, the situation of housing Mossoró is consistent with the national question in this regard. Among other reasons for this notion has been discussed on this site the presence of duality between city formal (legal) and informal city (illegal) housing and linked to it, as well as the self of the house as a procedure aimed at acquiring residence by social segments poorest. An argument guiding research was sustained on the paradox grounded in the notion that, although the owner of a collection of urban law and urban policy that covers the dwelling and its problems, there is an inherent difficulty in Mossoró by the power manager of the municipality of put into practice the laws available. As was noted, this restriction does not begin only with the entry into force of the Statute of the City, however it will be shown that this feature is favorable expression. Furthermore, it is important to emphasize that this is one more feature that relates directly Mossoró with the national situation. This is because, although this law ensures the consideration of urban property as endowed with social function that is consistent in the city as an expression of this prerogative Mossoró, his job this sense demonstrates difficulties for many reasons. Thus, it was found that since the first interventions of urban policy in the city, dating from the late 1960s, the solution of housing problems has been compromised. This assertion has legitimacy with the context of socio-spatial inequalities expressed in the processes of formation of spatial centrality and segregation, common in dynamic urban place. Thus, the diagnosis that exposes the housing problems, which reveals compromised quality of life of people living in social housing, this is, the poorest social segments of the local population. These classes, as shown by many indicators, are more vulnerable to infrastructure problems of housing, urban planning and restrictions that are the responsibility of the municipal administration.